UPAYA HUKUM TERHADAP PENOLAKAN PERMOHONAN PKPU DEVELOPER (STUDI KASUS PUTUSAN NOMOR 71/Pdt.Sus-PKPU/2024/PN Niaga Jkt.Pst): Legal Remedias Againts Court Rejection of Developer PKPU Petition (Case Study of Decision Number 71/Pdt.Sus-PKPU/2024/PN Niaga Jkt.Pst) - Erlinawati; Heru Pringgodani Sanusi (Reformasi Hukum Trisakti, 2025)
The rejection of the PKPU (Postponement of Debt Payment Obligations) petition against PT Karya Cipta Agung Persada, as decided in Case Number 71/Pdt.Sus-PKPU/2024/PN Niaga Jakarta Pusat, was based on the considerations of Supreme Court Circular Letter (SEMA) No. 3 of 2023. This rejection is deemed inconsistent with the formal requirements stipulated in Article 222 of Law No. 37 of 2004 concerning Bankruptcy and PKPU, particularly regarding the existence of due and collectible debt and the element of simple proof. The rejection raises legal concerns for creditors in obtaining certainty over the fulfillment of their rights. This research aims to examine: the legal basis for the court’s rejection of the PKPU petition in the aforementioned decision, and the legal remedies available to creditors following such rejection. The research employs a normative juridical method, relying on secondary data through literature review. Based on the analysis, it is concluded that the petition fulfilled the substantive requirements of PKPU, the court rejected it solely based on SEMA No. 3 of 2023, thereby limiting access to PKPU and bankruptcy proceedings for developers. Creditors, in response, may pursue legal remedies through a cassation appeal to the Supreme Court or by filing a breach of contract lawsuit before the District Court.